Ambivalensi Peran Birokrasi Negara Sebagai Pendukung Perjuangan Kelompok Perempuan dan Politik Gender Penguasa - Sofa Marwah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2011)
The Strugle Promote women requires cooperation of women groups with the state, throughthe device or the National Machineries, namely the state bureaucracy from top to bottom level. But there is ambivalence in this cooperation. On the one hand, gender mainstreaming mechanisms supported by National Machineries proved able to build a stable alliance with civil society group of women, especially in countries that have stable political economy. However, in developing countrie, the situation is likely to varry even pessimistic. Cooperation with the state has made a restriction to the changes, as well as to the choice of fighting for women's issues. As quoted Shirin M. Rai, the women's movement needs to work "in and against" state. In the context of Indonesia, gender politics imposed by the New Order in accordance with WID approach, and implemented by the state bureaucracy as a National Machineries. Meanwhile, authorities in the reform era has gradually been eroded such a case, by imposing a fixed GAD approach requires a critical role of the state bureaucracy.